ENGAGING INDONESIAN ELEMENTARY SCHOOL STUDENTS IN READING ACTIVITIES THROUGH WEB-BASED EDUCATIONAL GAMES - Angelica, Windyana; Afriani, Imro’atul Husna (English Language Teaching Methodology, 2024)
Reading interest among elementary school students is a critical factor in fostering literacy and academic success. However, traditional methods often struggle to capture student’s attention in increasingly digital learning environments. This study examines the impact of Wordwall, an online educational game, on increasing Indonesian elementary school students' interest in reading. Using a qualitative case study approach, the research investigates how interactive digital technologies, such as Wordwall, affect student motivation and vocabulary acquisition. Data were collected through classroom observations, interviews, and student feedback, focusing on a group of 5th-grade students. The results show that Wordwall transformed standard reading sessions into engaging, game-like experiences, making learning enjoyable and effective. The platform’s use of immediate feedback and visual aids helped improve student enthusiasm and vocabulary retention. This study highlights the potential of web-based educational games to create dynamic learning environments, improve student engagement, and address common challenges in Indonesian education, such as overcrowded classrooms and limited resources.